(untitled) (Povijesni prilozi (Historical Contributions), 2019)
The thaler of the queen and empress Maria Theresa, minted in her last regnal year of 1780, is one of the most famous silver coins in the world. Th aler is a type of large silver coin (around 40 mm in diameter, weighing around 30 g) that was used throughout Europe for almost 400 years. Because of its high quality and beautiful craft smanship, the thaler of Maria Theresa was in use as a trade coin from 1780 until as recently as the 1960s.